G06 Iron defect is implicated in white matter changes in Huntington disease. (29th August 2012) - Di Paola, M; Phillips, OR; Sanchez-Castaneda, C; Di Pardo, A; Maglione, V; Caltagirone, C; Sabatini, U; Squitieri, F
Abstract : Background: In normal condition, the concentration of iron in various region of the brain varies greatly. There is a progressive iron accumulation during the brain development (Zecca et al, 2004), with iron concentration increases in the brain until age 40 (Thomas and Jankovic 2004). The iron brain delivery is critical for its effects on fibre myelination, and iron restriction is associated with a general decline of myelin production (Todorich, et al, 2009). Aims: To investigate if WM callosal demyelination we have already found in HD (Di Paola et al, 2012) can be related to iron modification. Methods: HD patients (n=50) and controls subjects (CS) (n=50) underwent a multi-parameters MRI protocol, including 3D T1 acquisition and six consecutive T2*-weighted gradient echo-planar imaging sequence at different time of echo (Peran et al, 2010). Voxel-based morphometry and relaxometry analyses have been performed. Results: When pre-HD subjects were compared to HC, we did not detect any significant volume and iron content difference. When pre-HD subjects were compared to HD patients, callosal volume was reduced in the splenium, isthmus and posterior callosal body in HD, while the reduced iron content extended also more anteriorly involving the callosal body and the rostrum. When HD patients were compared to HC, we found a significantly global reduction of callosal volume with the iron content reduced mainly in the isthmus and part of splenium. Conclusions: Our findings suggest that WM damage in our HD subject can be strongly related to iron reduction content. It remains still open if the iron reduction is due to a failure in the repair myelin damage process or it is due to an abnormal brain development and myelination process.